Simultaneous Determination and Interactions between Investment, Financing and Remuneration Decisions - Mansour, Ammar Yaser; Taufil Mohd, Kamarun Nisham (UUM Press, 2010)
This study focuses on the internal determinants of the remuneration, financing, and investment decisions in an equilibrium setting. In addition explore the theoretical relationship between all three decisions simultaneously. Thus, the goal of this study is to add to the existing literature by presenting an equilibrium model of remuneration, financing and investment decisions. To the knowledge of the researcher this is one of the few studies in the literature to jointly model each decision in a simultaneous framework. Argue controlling for the endogeneity is important as it may help explain why previous studies report varying conclusions regarding the tests of certain hypotheses.